Screening Andaman Padauk (Pterocarpus dalbergioides) for drought tolerance - I, Jaisankar (Indian Journal of Agroforestry, 2023)
The coincidence of germination and seedling establishment with limited or no rainfall period is a major threat to the survival of Andaman Padauk (Pterocarpus dalbergioides), an endemic species of the Andaman Islands. This study has been conducted in a Completely Randomized Block Design (CRBD) with 6 replicates to identify the drought tolerant accessions among 14 accessions collected from different locations of the Islands. Drought stress has been induced in the 3-month-old seedlings by withholding irrigation for 1 month to observe the changes in the Relative Water Content (RWC), Chlorophyll Stability Index (CSI) and Epicuticular Wax Content (EPW) of leaves at regular intervals and Seedling Survival rate post-recovery period. After 28 days of imposed drought, seedlings of Accession No.8 collected from Mohanpur have recorded the highest RWC, CSI and EPW; and survival rate. On the other hand, seedlings of Accession No.13 collected from Yerata Jetty have recorded the lowest RWC and CSI; and seedlings of Accession No.12 collected from Danapur have recorded the lowest EPW and survival rate. The identified drought-tolerant seedlings have been planted in situ to check for their re-establishment.